Respect of the right to a fair trial in indigenous African criminal justice systems : the case of Rwanda and South Africa - Kotey, Nii Ashie (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2004.